Performance of SMES system with non‐linear dynamic evolution control approach for pulsed power load compensation. Issue 10 (25th March 2020) - Penthia, Trilochan; Panda, Anup Kumar; Patnaik, Nishant; Mohanty, Pratap Ranjan
Abstract : Superconducting magnetic energy storage (SMES) system is one of the efficient pulsed power compensators. Its response to the load fluctuations is faster and competent. This study proposes a non‐linear dynamic evolution control (NDEC) approach for SMES system. The control approach is implemented to regulate the error of three‐phase compensating current and DC‐link voltage. The control functions required for voltage source inverter (VSI) and bi‐directional DC–DC converter of the SMES system are derived using the NDEC control approach. A proportional–integral (PI) controller is replaced by the NDEC in the inner loop of a traditional pulse‐width‐modulation control strategy of VSI for the quick response and effective energy exchange. The elementary idea of implementing NDEC is to govern the system dynamics by maintaining a zero‐error state irrespective of load uncertainties quickly. Detrimental high rating stress on the system due to pulsed power load is substantially reduced with the proposed NDEC strategy. Source current is maintained almost balanced and harmonic‐free in order to ensure a quality and reliable supply to surrounding loads. The variation in source current is drastically reduced from 260 to 6% using the proposed system. Moreover, a comparative study between PI and NDEC‐based control scheme is presented using MATLAB simulation and experimental results.